Development of Quiz-Based Learning Evaluation on Theme 3 Subtheme 1 Class IV Students of Free Methodist 1 Private Elementary School - Martua Erikson Halomoan Silaban (Saniya Institute, 2024)
This study aims to develop a technology-based learning evaluation media Quiz on Theme 3 Subtheme 1 Class IV of SD Swasta Free Methodist 1 Medan, using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research method used is Research and Development. The evaluation instrument was validated by media and evaluation experts to ensure its quality. The validation results showed that this media was feasible and effective with some minor improvement suggestions. Students showed high enthusiasm during the Quiz-based evaluation, indicating that this media was not only effective but also interesting and relevant to learning. These findings support the application of technology in learning evaluation to increase student motivation and engagement.